2012
DOI: 10.1103/physreva.86.013810
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear spectroscopy with time- and frequency-gated photon counting: A superoperator diagrammatic approach

Abstract: We present a diagrammatic technique for calculating quantum-detected nonlinear optical signals using loop diagrams that act in the joint matter plus field space. This formalism, which is based on time ordered superoperators keeps track of the entangled matter plus field state, making it most suitable for spectroscopy applications. Photon counting is recast as a time and frequency convolution of a bare signal, which is given by a correlation function of matter, and a gating spectrogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 19 publications
0
47
0
Order By: Relevance
“…The other 'incoherent' contribution arises from the interaction with one of the two beams and scales quadratically in the pump intensity. Figure 7 depicts equation (36), where ω p is set on resonance with state f , versus the pump intensity |α| 2 .…”
Section: The Intensity Crossovermentioning
confidence: 99%
See 1 more Smart Citation
“…The other 'incoherent' contribution arises from the interaction with one of the two beams and scales quadratically in the pump intensity. Figure 7 depicts equation (36), where ω p is set on resonance with state f , versus the pump intensity |α| 2 .…”
Section: The Intensity Crossovermentioning
confidence: 99%
“…The time-and frequency-gated two-photon counting signal of beams a and b is given by a convolution of the 'bare signal' S B with the spectrograms W D of the two detectors [36,37],…”
Section: Time-and Frequency-gated Two-photon Countingmentioning
confidence: 99%
“…This is done to account for vacuum fluctuations caused by other field modes. However, we have recently shown [33] how the multipoint correlation function of the field is calculated in the joint field plus matter space given by the sum over Liouville space pathways. This microscopic method can account for all the effects of multiple vacuum modes by theses paths without adding a Langevin noise source.…”
Section: Discussionmentioning
confidence: 99%
“…[19], these commutator terms are not negligible and they are not properly incorporated in the filtering theory. Using the present superoperator approach formulated in the joint field plus matter space analysis we have earlier demonstrated that commutator terms are necessary for computing the relevant components of the nonlinear susceptibility in the parametric down conversion generation [33]. Furthermore, this approach allows to express all the correct features of the multipoint field correlation func-…”
Section: Simulationsmentioning
confidence: 97%
See 1 more Smart Citation